Effect of age on the morphologies of the human Schlemm's canal and trabecular meshwork measured with swept‑source optical coherence tomography. (October 2018) - Chen, Zhiqi; Sun, Jian; Li, Mu; Liu, Shiliang; Chen, Liugui; Jing, Sili; Cai, Zhen; Xiang, Yan; Song, Yinwei; Zhang, Hong; Wang, Junming
Abstract Purpose We aimed to measure the sizes of Schlemm's canal (SC) and the trabecular meshwork (TM) in healthy individuals and to evaluate variations with age from childhood to old age by using swept-source optical coherence tomography (OCT). Methods Anterior chamber angle imaging of the superior, inferior, nasal, and temporal regions of the right and left eyes was performed with swept-source OCT. The diameter and area of SC and TM width and thickness were measured manually from OCT images. Results A total of 114 healthy individuals were enrolled and included 48 male subjects and 66 female subjects; their ages ranged from 7 to 83 years. Both the SC diameter and area in the four quadrants decreased significantly with aging (P < 0.001) and were wider in the nasal and temporal quadrants compared with the superior and inferior quadrants. Changes in SC size showed significant positive correlations with axial length (AL) and anterior chamber depth (P < 0.001). There was a significant positive association between age and TM thickness in the nasal and temporal quadrants (P < 0.05). The inferior quadrant TM width was the widest among the quadrants. The superior quadrant TM thickness was the thinnest among the quadrants. Changes in TM thickness in the nasal and temporal quadrants showed a significant negative correlation with AL (P < 0.05). There was no statistically significant correlation in SC and TM parameters with central corneal thickness, intraocular pressure, sex, or right or left eye (P > 0.05). Conclusions With aging, the SC diameter and area became smaller, TM thickness increased, and TM width seemed to remain constant. Measurements of the sizes of SC and the TM with swept-source OCT could assist in clinical assessments and treatment planning for glaucoma.